Evaluasi Infrastruktur Jaringan LAN OPD Pemprov Bali dengan COBIT 5.0 Studi Kasus: Pemprov Bali - Budi Antara, Gde Made; Linawati, Linawati; Dewi Wirastuti, Ni Made Ary Esta (Majalah Ilmiah Teknologi Elektro, 2019)
The OPD LAN network infrastructure is used by users to access various services and applications that exist within the Bali Provincial Government, but in its operations there is no possibility of technical problems. Among 152 network disorders that occur during a year, it is known that the disorder that occurs in LAN OPD is more common in physical disorders (as many as 61 disorders) than logical disorders (as many as 24 disorders). In order to maintain the availability of OPD LAN network infrastructure, it is necessary to evaluate the OPD LAN network infrastructure using COBIT 5.0 which focuses on the EDM, DSS and MEA domains. The evaluation results of the OPD LAN network infrastructure resulted in a percentage index above 50%. Based on the ISO / IEC 15504 rating scale, the processes that are part of the EDM, DSS and MEA domains obtain L (Largely Achieved) status, which is still not fully achieved so that development and optimization of the current network infrastructure conditions are still needed. The results of the evaluation of network infrastructure that has been linked to the disturbance data record for a year, the process obtained in the EDM, DSS and MEA domains is recommended for development and optimization of DSS05, DSS01, DSS02, EDM03, DSS06, DSS03 and MEA02. The development and optimization is recommended towards the preparation of procedures in the form of integrated Standard Operational Procedure (SOP).